The Role of Peer Review in Enhancing Understanding of Domain Class Diagrams for Information Systems Undergraduates - Elvin Khoirunnisa (Publikasi Indonesia, 2025)
This study explores the use of peer review as a pedagogical strategy to improve undergraduate students’ understanding of domain class diagrams in an Information Systems course. The research examines students’ experiences and perceptions of peer feedback during a domain class diagram modeling task. Quantitative data were collected through a Likert-scale survey, while qualitative insights were gathered from open-ended responses. Findings show that students generally perceived peer review as beneficial for reinforcing conceptual understanding, promoting critical thinking, and identifying modeling errors. Most students rated the clarity, usefulness, and educational value of peer feedback highly, especially in supporting their comprehension of object-oriented principles. Students also reported gaining diverse perspectives, improving soft skills such as giving and receiving feedback, and deepening their understanding through observation and reflection. The study concludes that peer review can be a valuable learning tool in technical modeling contexts when accompanied by clear rubrics, guidance, and reflective practice.